Nano-engineering from Single Atoms to Gold Nanoclusters Anchored on MoS2 Nanosheets for an Efficient Hydrogen Evolution Reaction - Nichakarn Sornnoei; Kulpavee Jitapunkul; Panwad Chavalekvirat; Luckhana Lawtrakul; Pawin Iamprasertkun; Weekit Sirisaksoontorn; Tawan Sooknoi; Wisit Hirunpinyopas (ACS Applied Nano Materials, 2025)
Two-dimensional (2D) materials offer a versatile platform for catalyst-based applications. Decorating with single atoms and nanocluster engineering to increase the active sites can enhance the catalytic performance while minimizing the noble metal usage. Herein, we unveil the mechanism for an enhanced hydrogen evolution reaction (HER) when a gold nanocluster anchored on MoS2 nanosheets (MoS2/Au) is employed as an efficient electrocatalyst. By precisely tuning Au loading via electrodeposition (2–100 cycles), MoS2/Au-50 provides outstanding HER, exhibiting an ultralow overpotential of −184 mV (vs RHE) at 10 mA cm–2 with a low Tafel slope of ∼89 mV/dec and minimal charge transfer resistance, outperforming previously reported MoS2/Au catalysts. The enhancement is driven by electron transfer at the Au–MoS2 interface, which tailors the electronic structure toward more n-type conductivity, facilitating efficient HER kinetics. X-ray photoelectron spectroscopy reveals progressive shifts in the binding energies with an increase in gold deposition, as confirmed by density functional theory calculations, providing optimized bond energies. Moreover, MoS2/Au-50 also demonstrates remarkable catalytic stability at ultrahigh current density (>100 mA cm–2) for over 24 h, underscoring the potential of precision-engineered noble metal nanoclusters on 2D materials as scalable electrocatalysts for sustainable green hydrogen production.
Keywords: Electrocatalysts for Energy Conversion; Machine Learning in Materials Science; Nanocluster Synthesis and Applications